Simulation Of The Optimum Operating Conditions For A Propylene Glycol Production Unit Using Aspen Hysys Software - Alshbuki, Ezeddin (Journal of Pure & Applied Sciences, 2023)
Commercially, propylene glycol is produced by the direct hydrolysis of propylene oxide with water. This first-order, irreversible, exothermic reaction is performed in a glass-lined Continuous Stirred Tank Reactor (CSTR). In this study, the initiation of a CSTR was modelled from first principles and simulated using Aspen Hysys 3.2 to obtain concentration and temperature profiles. It is often very important how these profiles approximate the steady-state values. For example, when approaching a steady state the temperature may rise too high and this leads to degradation of the reactant or product, or the altitude may be unacceptable for safe operation. If either condition occurs, the system will exceed its practical stability limit. The practical stability limit represents the temperature above which it is undesirable to operate due to undesirable side reactions or equipment damage. Therefore, the best-operating conditions were obtained in terms of the flow rate of the raw material and the temperature of the reactor at 345 Kgmol/h and 82.2 °C on straight. The production of propylene glycol in the presence of an acid catalyst in an isothermal tank reactor is presented using advanced process simulation software. The effect of temperature was also calculated using the principle of energy balance on the reactor. The reactor operates optimally at a fractional conversion of 0.995 to obtain optimal values for the most important variables/parameters [reactor volume 7.92 m3, reactor length 2.83 m, reactor diameter 1.89 m, and amount of heat required for cooling per unit volume of the reactor 1205 kw].